VARIASI BAHASA PRESENTER PADA PROGRAM ACARA TEMBANG-TEMBUNG DI ADI TV - Suryono Suryono; Basuki Basuki (Universitas Sarjanawiyata Tamansiswa, 2017)
The aim of this research are (1) describe languages that presenter use on tembang-tembung program in ADITV ,and (2) describe the factors of languages variation that presenter use on tembang-tembung program in ADITV. This type of research is descriptive qualitative. Data in this research are using sentences which have language variation that presenter use on tembang-tembung program in ADITV. This data based on the using of languages on tembang-tembung program in ADITV. Metode of collecting data in this research is using observe metode, register technique, and observe , involve, speak technique. Analysis data metode in this research by using padan and agih metode. The result showed (1) the language that presenter use on tembang-tembung program in ADITV. (a) using of javanese languages, (b) Indonesian languages, (c) turn code, (d) mix code. (2) factors which cause languages variation presenter on tembang-tembung program in ADITV consist of (a) setting and scene. (b) participants,(c) ends,(d) act sequences, (e) key, (f) instrumentalities, (g) norms, (h) genre.